Analisis Faktor-Faktor Penyebab Kurangnya Ketertarikan Siswa Sekolah Menengah terhadap Pembelajaran Fisika Berdasarkan Kajian Literatur Pendidikan - Lela Sefita Sari; Junia Herlina; Melka Jasmita (Mataram University, 2026)
This study aimed to analyze the factors causing the lack of interest among secondary school students in learning physics based on a review of educational literature. The research employed a literature review method by analyzing eight scientific articles published between 2018 and 2025. The findings revealed that students’ low interest in physics learning is influenced by various factors, including the perception that physics is a difficult subject, the dominance of formulas and calculations, low learning motivation, and teaching methods that remain monotonous and teacher-centered. Several studies indicated that more than 60% of students had a low level of interest in learning physics, while approximately 65% experienced difficulties in understanding abstract physics concepts. In addition, the limited availability of interactive learning media and laboratory facilities contributed to students’ low participation in physics learning. Data from several studies showed that the use of technology-based learning media and contextual learning approaches could increase students’ interest in learning by more than 70%. Based on the review findings, it can be concluded that both internal and external factors significantly influence students’ interest in physics learning. Therefore, more interactive, creative, and contextual learning innovations are needed to enhance students’ engagement and interest in physics.